Chromatin genes and disease - Gibbons, Richard (Henry Stewart Talks, 2014)
Chromatin genes and disease, Epigenetics: the phenotype reflects the pattern of gene expression, The role of chromatin in epigenetic regulation, Epigenetic factors and their role in gene expression, Human diseases involving epigenetic factors